2011
DOI: 10.1021/bi102023x
|View full text |Cite
|
Sign up to set email alerts
|

How Does the QB Site Influence Propagate to the QA Site in Photosystem II?

Abstract: The redox potential of the primary quinone Q(A) [E(m)(Q(A))] in photosystem II (PSII) is lowered by replacement of the native plastoquinone (PQ) with bromoxynil (BR) at the secondary quinone Q(B) binding site. Using the BR-bound PSII structure presented in the previous Fourier transform infrared and docking calculation studies, we calculated E(m)(Q(A)) considering both the protein environment in atomic detail and the protonation pattern of the titratable residues. The calculated E(m)(Q(A)) shift in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…). There, the electron affinities of the primary and secondary acceptor plastoquinones Q A and Q B , the factors that control them, and the sequence of reduction and protonation of Q B are questions with critical implications for biological photosynthesis, and remain open challenges for both experiment and theory …”
Section: Methodology and Computational Detailsmentioning
confidence: 99%
“…). There, the electron affinities of the primary and secondary acceptor plastoquinones Q A and Q B , the factors that control them, and the sequence of reduction and protonation of Q B are questions with critical implications for biological photosynthesis, and remain open challenges for both experiment and theory …”
Section: Methodology and Computational Detailsmentioning
confidence: 99%
“…The authors observed more substantial contribution of the non-covalent interactions of Q A head group with D2-Phe261 and D2-Trp253 and Q B head group with D1-Phe255 and D1-Phe265 to the total PQ binding energies than the above mentioned H-bonding. Instead, it has been unambiguously demonstrated the importance of the H-bonding patterns of PSII PQs in determining their redox potential [40, 41]. The relative contribution of PSII integral lipids and cofactors to the total Q B interaction energy is less than 20% and is mainly limited to the PQ tail (Table 1 and Table 2 ).…”
Section: Psii Plastoquinonesmentioning
confidence: 99%
“…Within the PSII RC, the rapid release of an electron from the reaction center P680 to a pheophytin (Pheo) molecule produces the charge separated state, P680 + Pheo − (3). Two quinones, Q A and Q B , are located at the acceptor side of PSII with a H‐bounded nonheme iron in between (4). Charge stabilization takes place through electron transfer from Pheo − to the primary quinone acceptor, Q A , in less than 200 ps (5) and reduction of the cationic radical P680 + by Y Z (tyrosine 161 of D1 subunit), in 10–500 ns (6).…”
Section: Introductionmentioning
confidence: 99%
“…Charge recombination in PSII can be analyzed by thermoluminescence (TL) in pre‐illuminated photosynthetic materials such as intact leaves, isolated thylakoid membranes, or PSII submembranes fractions (14,15). Charge recombination of P680 + Q A − is known to occur probably via the intermediate state P680 + Pheo − (4). However, this type of recombination cannot be studied by themoluminescence.…”
Section: Introductionmentioning
confidence: 99%